2004
DOI: 10.1111/j.0307-6962.2004.00386.x
|View full text |Cite
|
Sign up to set email alerts
|

Honeydew amino acids in relation to sugars and their role in the establishment of ant‐attendance hierarchy in eight species of aphids feeding on tansy (Tanacetum vulgare)

Abstract: Abstract.  The ratio of the concentration of honeydew total amino acids to total sugars in the honeydew of eight species of aphids, all feeding on tansy, Tanacetum vulgare (L.), was determined and correlated with honeydew production and ant‐attendance. The honeydew of the five ant‐attended aphid species [Metopeurum fuscoviride (Stroyan), Trama troglodytes (v. Hayd), Aphis vandergooti (Börner), Brachycardus cardui (L.), Aphis fabae (Scopoli)] was rich in total amino acids, ranging from 12.9 to 20.8 nmol µL−1 co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
110
1
3

Year Published

2005
2005
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(114 citation statements)
references
References 49 publications
0
110
1
3
Order By: Relevance
“…8% fructose and 6% glucose in the 20% solution and 31% fructose and 25% glucose in the 80% solution) and small (mean = 0.053 g) and large (mean = 0.36 g) crickets. The sugars found in clover honey, glucose, and fructose are the main components of the honeydew and nectars exploited in natural communities (Blüthgen & Fiedler, 2004;Woodring et al, 2004) and the concentrations we used fall towards the ends of the spectrum found in nature (Blüthgen & Fiedler, 2004). The crickets were representative of the proteinaceous resources frequently exploited by ants.…”
Section: Experimental Designmentioning
confidence: 99%
“…8% fructose and 6% glucose in the 20% solution and 31% fructose and 25% glucose in the 80% solution) and small (mean = 0.053 g) and large (mean = 0.36 g) crickets. The sugars found in clover honey, glucose, and fructose are the main components of the honeydew and nectars exploited in natural communities (Blüthgen & Fiedler, 2004;Woodring et al, 2004) and the concentrations we used fall towards the ends of the spectrum found in nature (Blüthgen & Fiedler, 2004). The crickets were representative of the proteinaceous resources frequently exploited by ants.…”
Section: Experimental Designmentioning
confidence: 99%
“…Other species, for example Macrosiphoniella tanacetaria on tansy, contain virtually no melezitose in their honeydew, and are not usually tended by ants (Hendrix et al, 1992;Völkl et al, 1999). In a recent study on the hierarchy of antattendance in eight species of aphids feeding on tansy (Woodring et al, 2004) it was demonstrated that a combination of the sugar richness of the honeydew excreted by the aphid (rate of honeydew production × total sugar concentration in the honeydew) together with a high content of the attractant sugar melezitose determines the extent of ant-attendance. There was no evidence that any single amino acid or group of amino acids in the honeydew act as an attractant for ant-attendance in these aphids.…”
Section: Albummentioning
confidence: 99%
“…However, in the current study total nitrogen concentration was the same for the phloem fluid of plants with or without flowers, and therefore we do not believe that honeydew from membracids feeding on plants with or without flowers would vary in nitrogen concentration. Although ants may assimilate amino acids from hemipteran honeydew (Woodring et al, 2004), sugar concentration and composition appear to be the most important factors mediating the interaction between ants and Hemiptera (Kiss, 1981).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, sugar concentration and composition appear to be the primary attractants for honeydew-gathering ants (Völkl et al, 1999;Fischer & Shingleton, 2001) and recent studies indicate that the amino acids in the honeydew of several aphid species do not influence ant attendance (Woodring et al, 2004; but see Lanza, 1988;Bristow & Yanity, 1999). Moreover, the main source of protein for many ants involved in these interactions, including Camponotus species, is live prey or dead animal matter (Buckley, 1987;Hölldobler & Wilson, 1990;Davidson et al, 2003, and references therein).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation